Priority factors for development of Bantaragung as sustainable tourism village - I Made Adhi Gunadi; Dhike Noordestiasari Hanurajasa; Riza Firmansyah (Universitas Merdeka Malang, 2022)
Bantaragung Village in Majalengka Regency, West Java is one of the tourism villages which raises the diversity and uniqueness of its natural potential as an attraction. As a developing tourism village, it is necessary to ensure that the development of Bantaragung Tourism Village is in accordance with the principles of sustainable tourism. Therefore it is important to know and determine the main priority factors for the development of Bantaragung as a sustainable tourism village. The purpose of this research is to identify the characteristics of tourism village, to analyze the development priorities and to describe the sustainable tourism development strategy in Bantaragung Village. Analytical Hierarchy Process (AHP) using Expert Choice 11 Software and SWOT analysis are the methods used in this research. The results show that from the seven criteria for tourism village, accessibility has the dominant level of importance of the tourism village characteristic. As for the 4 alternative choices of natural tourist attractions, Awilega Camping Ground is the top priority for natural tourism attractions in Bantaragung. Furthermore, this study also found that the strategy for sustainable tourism development is to combine the existing strengths and threats elements of Bantaragung. In other words, the strategies could be implemented by preserving traditional culture and arts, as well as creating a distinctive feature in the Awilega Camping Ground.